Karcinom ledviny v ére nastupujících robotických technologií - Kolombo, Ivan; Ponesický, Jirí; Toberný, Michal; Kríz, Radko; Zemanová, Iva; Weichet, Jirí; Vymazal, Josef; Cernohorský, Stanislav; Bartůnek, Milan (Casopis lekaru ceskych, 2011)
Renal cell carcinoma is the most malignant urological tumour and the incidence in the Czech Republic is currently highest in the world. Kidney cancer is associated with seven different genes and is characterized nowadays as metabolic disease. Authors present some current facts about advances in diagnosis and new treatment methods. Different findings required individual approach. Diagnosis improved with more sophisticated ultrasonography, computed tomography, magnetic resonance imaging and positron emission tomography etc. Apart from standard surgery new alternative methods of minimally invasive procedures also assert (laparoscopy, robotic surgery, radiofrequency ablation, kryoablation) and are incorporated in current complex treatment strategies. Systemic therapy with new targeted antiangiogenics drugs is a new standard of treatment for metastatic kidney cancer Complex care with integration of local treatment (surgery, radiotherapy, selective embolization, radiosurgery, cementoplasty, vetrebroplasty etc.) and systemic medication with best supportive care is optimal for a metastatic kidney cancer. More accurate diagnostic methods and complex interdisciplinary approach with integration of systemic therapy with new targeted drugs and new minimally invasive procedures represent new possibilities for patients with kidney cancer.
Keywords: nádory ledvin; robotika; kombinovaná terapie; Carcinoma, Renal Cell; Kidney Neoplasms; Combined Modality Therapy; Humans; lidé; Robotics; karcinom z renálních buněk